The Mediatization Of Religion In News Narratives On Religious Tolerance In NU Online: A Corpus Linguistics Analysis - Septiani, Eka; Ocvita Ardhiani; Thenatha Lintang A; Ulva Lathifah (KOMUNIKA, 2025)
Indonesia is a pluralistic nation composed of diverse ethnicities, religions, and cultures. This diversity makes religious tolerance a vital pillar in maintaining national unity. Amid the challenges of pluralism, media plays a strategic role in shaping public discourse on national and religious values. This study aims to analyze the representation of religious tolerance in the news narratives of NU Online using a corpus linguistic approach. Referring to Stig Hjarvard’s theory of mediatization, this study views digital media as an institution with its own internal logic while simultaneously functioning as part of other social institutions, such as religion. A total of 50 articles related to the theme of tolerance, published on NU Online between June 2023 and June 2025, were analyzed using Voyant Tools to examine word frequency, collocation, and concordance patterns. The findings reveal that the words “tolerance,” “religion,” “Indonesia,” “Islam,” and “NU” were the most dominant. Collocations such as “religious tolerance” and “interfaith tolerance” highlight discursive patterns that reinforce the image of moderate Islam promoted by NU Online. This study affirms that NU Online not only communicates religious messages but also actively constructs social realities related to tolerance through the digital media logic. These findings contribute to understanding how moderate Islamic media constructs tolerance discourse in the digital age and can inform media literacy initiatives.